Women's experiences of safety apps for sexualized violence: a narrative scoping review - Nicole Doria; Christine Ausman; Susan Wilson; Annalisa Consalvo; Jad Sinno; Leah Boulos; Matthew Numer (BMC, 2021)
Abstract Background Sexualized violence against women is a significant human rights problem worldwide. Safety apps have the capacity to provide women with resources to prevent or respond to experiences of sexualized violence. Methods The aim of the following study was to review the scope of the literature on women's experiences of safety apps related to sexualized violence. The databases Embase, MEDLINE, PsycINFO, and Scopus were systematically searched, and seven studies were included in this review. Results Thematic analysis identified the following themes in the literature: (1) security; (2) accessibility; and (3) knowledge. Conclusion The gaps in the literature are identified and implications and recommendations for future research is discussed.